Parenting patterns in developing the disciplinary character of upper grade students in elementary schools - Cahyani, Eka Nur; Al Fikri, Muhammad Arif (Universitas Riau Kepulauan, 2024)
The aim of writing this article is to find out 1) parenting patterns in developing the disciplinary character of upper class students at the Duren 03 State Elementary School, Tengaran District 2) the obstacles experienced by parents in developing the disciplinary character of upper class students at the Duren State Elementary School 03 Tengaran District 3) efforts made by parents in developing the disciplined character of upper class students at Duren State Elementary School 03 Tengaran District. This type of research is qualitative research. The data collection techniques used were interviews, observation and documentation. The data analysis used is in the form of data reduction, data presentation, and drawing conclusions. Checking the validity of the data in this research takes the form of source triangulation and technical triangulation. The results of this research are 1) parents' parenting patterns in developing the disciplined character of upper class students mostly use democratic parenting, with this parenting style children can show a disciplined character in themselves, 2) the obstacles parents encounter in developing students' disciplined character The upper class is the job of parents who have work demands from morning to afternoon or evening. So this work also becomes an obstacle for parents, resulting in reduced time spent together with family. As well as the influence of globalization (TV, cellphones or online games), 3) the efforts made by parents to develop the disciplined character of upper class students are mostly through family consistency, implementing children's daily rules or routines and teaching children to be empathetic.